The Kv1.3 ion channel acts as a host factor restricting viral entry. Issue 2 (10th September 2020) - Lang, Yange; Li, Fangfang; Liu, Qiang; Xia, Zhiqiang; Ji, Zhenglin; Hu, Juan; Cheng, Yuting; Gao, Minjun; Sun, Fang; Shen, Bingzheng; Xie, Chang; Yi, Wei; et al.
Abstract: Virus entry into cells is the initial stage of infection and involves multiple steps, and interfering viral entry represents potential antiviral approaches. Ion channels are pore‐forming membrane proteins controlling cellular ion homeostasis and regulating many physiological processes, but their roles during viral infection have rarely been explored. Here, the functional Kv1.3 ion channel was found to be expressed in human hepatic cells and tissues. The Kv1.3 was then revealed to restrict HCV entry via inhibiting endosome acidification‐mediated viral membrane fusion. The Kv1.3 was also demonstrated to inhibit DENV and ZIKV with an endosome acidification‐dependent entry, but have no effect on SeV with a neutral pH penetration. A Kv1.3 antagonist PAP‐1 treatment accelerated animal death in ZIKV‐infected Ifnar1 −/− mice. Moreover, Kv1.3‐deletion was found to promote weight loss and reduce survival rate in ZIKV‐infected Kv1.3 −/− mice. Altogether, the Kv1.3 ion channel behaves as a host factor restricting viral entry. These findings broaden understanding about ion channel biology.